POLA INTERAKSI PEDAGANG KONSINYASI DENGAN PEMILIK WARUNG DI KECAMATAN TONDANO SELATAN, PROVINSI SULAWESI UTARA - Mesra, Romi; Marsa, Yummy Jumiati; Putri, Mardiati Etika (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The author who is directly involved in the consignment trading process sees so many phenomena that occur, whether it is related to the consignment trader, the shop owner, the emotional relationship between the two, business relationships, character, cultural values, and so on. The research approach used in this study is qualitative research approach. Data collection techniques in this study were carried out by in-depth interviews and observations. The types of data in this study are: primary data and secondary data. Data analysis techniques in this study use data analysis techniques miles and hubermen, including data reduction (data reduction), data presentation (data display) and drawing conclusions and verification (conclusion drawing / verification). The results of this study indicate that there are 7 patterns of interaction between consignment traders and shop owners, namely: making mutually beneficial business agreements, cooperation on the basis of mutual trust, mutual understanding of each other's character, respecting different cultures, disputes for breaking the agreement, lack of openness, and conflict of interest.